Training Intervention Using Sit-Up and Bent Arm Full Over Methods to Improve Lob Shot Execution in Badminton Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study investigated the effectiveness of a training intervention using sit-up and bent arm full-over methods to improve lob shot execution in badminton athletes at PKO FIKK UNM. A quasi-experimental design with pre-test and post-test control group was employed, involving 20 active badminton athletes divided equally into experimental and control groups. The intervention lasted 6 weeks, with 3-4 training sessions per week focusing on core and shoulder muscle strengthening exercises. Results showed a significant improvement in the experimental group’s lob shot performance. The mean post-test score increased from 70.3 (SD = 5.1) to 85.4 (SD = 4.2), with a paired sample t-test confirming the change as statistically significant (t(9) = 8.72, p < 0.001). Conversely, the control group’s scores showed no significant change (pre-test Mean = 69.8, SD = 4.9; post-test Mean = 71.0, SD = 5.3; t(9) = 1.12, p = 0.29). Independent sample t-tests between groups showed a significant difference in post-test results favouring the experimental group (t(18) = 6.04, p < 0.001). The effect size (Cohen’s d = 1.91) indicated a large practical impact of the training intervention. This study supports the integration of sit-up and bent arm full-over exercises into badminton training programs to enhance lob shot technique through improved muscular strength and control. Future research is recommended to explore long-term effects and applicability to other badminton skills.